Measurement Tools To Manage Customer Relationship Operations In Iraqi Banks Transactions And Their Role In Enhancing Customer Loyalty - Ibrahim Al-Mashhadani, Ahmed Ismaail (Opción, 2019)
Purpose: Due to the failure of customer relationship management (CRM) in bank- ing transactions in the public and private sector, which led to weak loyalty to the customer, which can be solved by improving the better measure of customer rela- tionship management process, the purpose of this research is to identify customer relationship management processes within banks Sample research, and propose a tool for measuring customer relationship management (CRM). DESIGN / METH- ODOLOGY / APPROACH: A field study was conducted in the Iraqi banks. The research was designed according to the development of the existing standards in the literature. The descriptive method was used by using the questionnaire which was distributed to 58 individuals. Results: The research provides a general under- standing of customer relationship management processes in a customer-oriented perspective and ultimately customer loyalty and trust towards the service provid- er. The measurement tool proposes seven main processes: Targeted management, extensive information management, customization, expansion management, refer- rals, termination management, win win management. Operational Implications: Analysis results provide useful information for managers to identify, measure and improve the customer relationship management process to achieve customer satis- faction and increase their loyalty. Originality / Importance: This paper presents a review of customer relationship management measurement literature and its rela- tion to customer loyalty. Based on this review, the research identifies seven custom- er relationship management processes to assess customer relationship management in the surveyed banks.